Социальное образование и его роль в развитии общества (Путеводитель предпринимателя, 2020)
Article is devoted the analysis of the developed tendencies in social formation of Russia. Problems of a professional training with the higher vocational training for system of social protection of the population are considered both from a position of applied sociology, and from an expert-manager position. The author offers concrete ways of increase of efficiency of social formation which are defined by practical requirement of social establishments.